MENINGKATKAN DAN MEMPROMOSIKAN UMKM MELALUI PRODUK KERIPIK TALAS DI DESA BUWUN SEJATI KECAMATAN NARMADA LOMBOK BARAT - Farmasari, Santi; Akbar, Ahmad Naufal; Aenalia, Aenalia; Pariha, Ana; Nazofha, Baiq Reghina Fidya; Apriana, Emi; Elfiza, Era Meizaton; Fitriani, Fitriani; Suryani, Lili; Amin, Muhammad Rizal; Fauzi, Safira (Jurnal Wicara, 2023)
MSMEs are defined as trading businesses whose management is handled by people or business entities with a small or micro scope in general. Experts identify micro, small and medium enterprises as small businesses that help advance the country's economy. The economic growth of a country or region, especially Indonesia, is highly dependent on Micro, Small and Medium Enterprises (MSMEs). Buwun Sejati Village is one of 21 villages in Narmada District. Buwun Sejati Village has an area of 213.08 hectares with a population of 4,403 people consisting of 2,220 men and 2,183 women with 1,368 household heads. Based on these considerations, the KKN Desapreneur of Buwun Sejati Village seeks to facilitate community empowerment activities by proposing activities that can be carried out by the surrounding community, namely by developing MSME Taro Chips products, so as to be able to improve the economy of the Buwun Sejati villagers.